2017
DOI: 10.1016/j.jmb.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Guide to the MAGE Family of Ubiquitin Ligases

Abstract: Melanoma antigen (MAGE) genes are conserved in all eukaryotes and encode for proteins sharing a common MAGE homology domain. Although only a single MAGE gene exists in lower eukaryotes, the MAGE family rapidly expanded in eutherians and consists of more than 50 highly conserved genes in humans. A subset of MAGEs initially garnered interest as cancer biomarkers and immunotherapeutic targets due to their antigenic properties and unique expression pattern that is primary restricted to germ cells and aberrantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
124
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 202 publications
(290 reference statements)
0
124
0
1
Order By: Relevance
“…The melanoma antigen gene (MAGE) protein family includes more than 40 genes, many of which are cancer-testis antigens (CTAs) [1,2]. These proteins share a common MAGE-homology domain that is conserved throughout eukaryotes and structurally forms tandem winged-helix motifs [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The melanoma antigen gene (MAGE) protein family includes more than 40 genes, many of which are cancer-testis antigens (CTAs) [1,2]. These proteins share a common MAGE-homology domain that is conserved throughout eukaryotes and structurally forms tandem winged-helix motifs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…An important advance to understanding the function of MAGEs was made when we discovered that MAGE proteins are positive regulators of E3 RING ubiquitin ligases [3]. MAGE proteins bind specific RING proteins to form stable multi-subunit E3 ubiquitin ligase complexes known as MAGE-RING ligases (MRLs); more than 50 MRLs have since been identified [1]. Mechanistic studies of a few MRLs have demonstrated the ability of MAGEs to function as substrate specificity factors [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the molecular mechanisms regulating G3BP concentration and whether different cell types and disease states fine-tune G3BP concentration to alter stress tolerance remain unknown. Melanoma antigen (MAGE) genes encode a family of proteins sharing a common MAGE homology domain (MHD) (Lee and Potts, 2017). Following the emergence of eutherian mammals, the MAGE family underwent a rapid expansion from a single MAGE in lower eukaryotes to more than 50 genes in humans (Lopez-Sanchez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most MAGEs, including MAGE-B2, are located on the X-chromosome and are classified as cancer-testis antigens (CTAs) given that they are primarily expressed in the testis but are aberrantly expressed in cancers (Chomez et al, 2001;Fon Tacer et al, 2019;Weon and Potts, 2015). A growing body of studies have revealed that MAGEs assemble with E3 RING ubiquitin ligases to form MAGE-RING ligases (MRLs) and act as regulators of ubiquitination in diverse cellular and developmental processes (Doyle et al, 2010;Lee and Potts, 2017). However, the functions of most MAGEs, including MAGE-B2, have not been fully elucidated and their study has been primarily restricted to cancer cells (Peche et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…MAGEL2 has elevated expression in the hypothalamus and functions within a multi-subunit protein complex, which consists of MAGEL2, the TRIM27 E3 ubiquitin ligase, and the USP7 deubiquitinating enzyme. This complex is critical to the cellular process of recycling membrane proteins from endosomes through the retromer sorting pathway via ubiquitination and activation of the WASH actin nucleation promoting factor [1].…”
Section: Introductionmentioning
confidence: 99%